PENGARUH SALES GROWTH, PERPUTARAN KAS DAN LIKUIDITAS TERHADAP PROFITABILITAS PERUSAHAAN (Studi Empiris Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek IndonesiaTahun 2017-2019) - Elisa Rosanti Sinaga; La Ane (Niagawan, 2021)
The problem in this study is the company's profit which is very important for the company because it is the company's main goal.  The purpose of this study was to examine the effect of the variables of sales growth , cash turnover and liquidity on profitability in manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2017-2019. The population in this study amounted to 180 manufacturing companies listed on the Indonesia Stock Exchange in 2017-2019. The sampling method used is purposive sampling, with a research sample of 27 companies for 2017-2019, so the research sample data is 81. The data collection technique is to download financial reports from the www.idx.co.id site. The data analysis technique used in this study used multiple regression analysis. The results of the study partially show that sales growth variable has no significant effect on profitability, but the cash turnover and liquidity variables have a partial and significant effect on the company's profitability. Simultaneously sales growth, cash turnover and liquidity have a positive and significant effect on profitability.